2018
DOI: 10.1111/apm.12833
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vascular malperfusion of the placental bed

Abstract: Maternal vascular malperfusion (MVM) of the placental bed represents a recognizable pattern of placental injury related to altered uterine and intervillous blood flow. MVM consists of a constellation of placental pathologic findings seen in the maternal decidual vessels, reflecting abnormal spiral artery remodeling, as well as in the villous parenchyma, reflecting abnormalities in oxygenation and flow dynamics in the intervillous space. This review is dedicated to the gross pathology, microscopic pathology, up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
148
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(167 citation statements)
references
References 48 publications
11
148
2
6
Order By: Relevance
“…According to this classification system, early FGR is associated with increased rates of preeclampsia, abnormal umbilical Doppler results, fetal hypoxia, and neonatal mortality and morbidity compared with late growth failure . Although this classification can be of practical value, helping to establish surveillance protocols to monitor fetal well‐being, the characteristics of placental lesions, including the different types and their distribution, leading to different growth failure patterns are yet to be elucidated . In addition, preeclampsia and abnormal Doppler velocimetry of umbilical vessels are associated with distinct placental lesions, suggesting that the frequency and severity of FGR‐associated placental lesions could be influenced by the occurrence of other complications …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to this classification system, early FGR is associated with increased rates of preeclampsia, abnormal umbilical Doppler results, fetal hypoxia, and neonatal mortality and morbidity compared with late growth failure . Although this classification can be of practical value, helping to establish surveillance protocols to monitor fetal well‐being, the characteristics of placental lesions, including the different types and their distribution, leading to different growth failure patterns are yet to be elucidated . In addition, preeclampsia and abnormal Doppler velocimetry of umbilical vessels are associated with distinct placental lesions, suggesting that the frequency and severity of FGR‐associated placental lesions could be influenced by the occurrence of other complications …”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiologic mechanisms of placental injury leading to FGR involve a reduction in trophoblastic invasion of the decidua and a failure of spiral artery transformation, which cause decreased maternal blood flow into the intervillous space . Subsequent persistent ischemia/reperfusion events and maternal tissue repair mechanisms are both related to developmental placental defects (eg, decidual arteriopathy) and malperfusion lesions (eg, infarcts and syncytial nodes) . Previous studies that have evaluated the rates of placental lesions suggestive of maternal vascular underperfusion among pregnancies with fetal growth defects are mainly retrospective in design, and are carried out in small‐for‐gestational‐age infants rather than in sonographically diagnosed fetal growth failure .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These features are characteristic of preeclampsia with severe features; they also occur in women with chronic hypertension. 7 Because the thrombi had no hyalinization, they were recent (within several days), caused by her TTP exacerbation. Confocal microscopy images of immunostained placental sections demonstrated that the thrombi were primarily composed of von Willebrand factor (VWF) (Figure ).…”
Section: Case Presentationmentioning
confidence: 99%